Non-Linear Dynamics in the Beat-to-Beat Variability of Sympathetic Activity in Decerebrate Cats - Porta, A.; Baselli, G.; Montano, N.; Gnecchi-Ruscone, T.; Lombardi, F.; Malliani, A.; Cerutti, S. (Methods of Information in Medicine, 1994)
Non-linear interactions between low-frequency rhythms (0.1 Hz) of beat-to-beat variability series of sympathetic discharge and respiratory rhythm (0.3 Hz) are observed in decerebrate artificially ventilated cats. Simple graphical tools as Poincare and recurrence maps are used to detect, in a qualitative way, phase-locking phenomena. Non-parametric bispectral analysis is also carried out to quantify the degree of second-order coupling between oscillations at different frequencies.
Keywords: Sympathetic Discharge; Ventilation Cycle; Non-linear Coupling